“Der Ehehimmel begann schon früh sich zu trüben”: Interdenominational Comparison of Divorce Proceedings - Stalder, Birgit (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
The following paper is based on the first provisional results of my doctoral dissertation. For about two years I have been working on an interdenominational comparison of legal records of divorce proceedings. I’ve been comparing resolution records of the civil court in Berne, a Protestant town in a Protestant canton of Switzerland, with the same kind of documents written at the civil court of Freiburg, a Catholic town in a Catholic canton. Courts are places of social negotiation, where norms are discussed and socially accepted gender-specific behavior is constructed. Divorce cases, in particular, reveal a lot about the relationship between the sexes and about the historical ideas of what a man is and what a woman is. This approach, close to historical anthropological research, begins with the couple and the balance of power in daily life, from whence I try to expand my knowledge to cover a macro-historical level. I want to know more about the increasing state influence on private institutions such as marriage and family by means of laws and norms and about con-cepts of gender in this period. These concepts not only concern the couples I look at, but they also have an influence on society in general and its structures. The interdenominational comparison is a new point of view as far as divorce records are concerned. It is an important aspect when one works with documents of the 19th century in the field of Swiss legal History. In 1848, the modern Swiss Confederation was founded after a short war between the supporters of a political centralization, mostly the liberal, Protestant cantons, and the opponents of the new political system, the conservative, Catholic cantons. During the last third of the 19th century this conflict, Kulturkampf, arose again, but only on a political and mental level. The Protestants accused the Catholics of being guided by the Pope and tried to hold them back wherever they could. The Catholics felt suppressed and felt that their traditional values were given away.